Toward an Indigenist Ecology of Knowledges for Canadian Literary Studies - Coleman, Daniel (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2012)
Critics such as Marie Battiste, Lee Maracle, Sákéj Henderson, and Lewis Gordon have called attention to how knowledge was and is a central target of colonial domination, as well as to how the other side of genocide is epistemicide. With this troubling history of “cognitive imperialism” (Gordon) in mind, Boaventura de Sousa Santos, João Arriscado Nunes, and Maria Paula Meneses insist that “there is no global social justice without global cognitive justice” and the “monoculture of [Western] scientific knowledge” must be replaced with an “ecology of knowledges.” For such a critical approach to be developed in a way that would be relevant for Canadian literary criticism, and to contribute to an ethical space of study, the genealogies underpinning Eurocentric knowledge systems must be questioned, and the kinds of Indigenous knowledge that have been suppressed and dismissed through them must be reconsidered.